2013
DOI: 10.1097/ta.0b013e3182a924f2
|View full text |Cite
|
Sign up to set email alerts
|

Group VIB Ca2+-independent phospholipase A2γ is associated with acute lung injury following trauma and hemorrhagic shock

Abstract: The iPLA(2γ) enzyme is possibly involved in the pathogenesis of ALI following T/HS through the mesenteric lymph pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Studies have shown that the biologic activity of the ML is directly correlated with the inflammatory response of immune cells that lead to remote organ injury, such as ALI (5,6). Moore et al and others have demonstrated that the lipid fraction extracted from postshock ML activates systemic neutrophils, increases endothelial cell permeability, and contributes to lung injury after T/HS (4,7,8). On the other hand, D'Alessandro et al (9) have demonstrated that the protein fraction of ML is not only altered by T/HS but also has the ability to activate neutrophils, suggesting that the protein component may also contribute to the postshock SIRS pathophysiology.…”
mentioning
confidence: 99%
“…Studies have shown that the biologic activity of the ML is directly correlated with the inflammatory response of immune cells that lead to remote organ injury, such as ALI (5,6). Moore et al and others have demonstrated that the lipid fraction extracted from postshock ML activates systemic neutrophils, increases endothelial cell permeability, and contributes to lung injury after T/HS (4,7,8). On the other hand, D'Alessandro et al (9) have demonstrated that the protein fraction of ML is not only altered by T/HS but also has the ability to activate neutrophils, suggesting that the protein component may also contribute to the postshock SIRS pathophysiology.…”
mentioning
confidence: 99%
“…Therefore, we determined the minimum sample size (n = 3) according to our prior studies that evaluated the concentration of arachidonic acids in the ML in an intestinal ischemia-reperfusion model. 13,16 Although rats dying during the experiments were planned to be excluded from the analysis, all three rats survived until the end of the experiments and were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The effect size could not be estimated before the experiments because we did not have data demonstrating the concentration of lipid metabolites derived from gut microbiota in the ML. Therefore, we determined the minimum sample size (n = 3) according to our prior studies that evaluated the concentration of arachidonic acids in the ML in an intestinal ischemia-reperfusion model 13,16 . Although rats dying during the experiments were planned to be excluded from the analysis, all three rats survived until the end of the experiments and were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure the reliability of the results, we performed a power analysis before conducting all the experimental work according to the methods used in one of our previous studies. 15 In this past study, we evaluated AA in the ML before and after I/R using mass spectrometry. The AAvalue increased 2.55 times with an SD of approximately 0.26.…”
Section: Discussionmentioning
confidence: 99%